From Semiotics to Latour and back. Trajectories of an Open Dialogue - Peverini, Paolo (E|C, 2023)
Hybrid is not a term belonging to the metalanguage of semiotics, so why pay attention to this notion from the perspective of the study of signification? There are at least two reasons, and they are interconnected. The first concerns the growing diffusion of this term in the sphere of both academic research and public debate. Faced with the proliferation of this term (it is worth remembering that it is anything but recent), semiotics is called into question as a discipline founded on the development of rigorous procedures for decomposing and analysing the phenomena of signification in the service of a critique of culture, following the hypothesis that the circulation of the word hybrid is the outcome of logics of production and circulation of meaning that are anything but obvious. The widespread diffusion of this term, therefore, can only urge semiotic research to measure itself against a widespread and persistent anthropocentric prejudice, based on the presumed primacy of human action, which irreconcilably distinguishes and separates subjects and objects, nature and culture, questioning the persistence of a dichotomy whose fallacy has long been at the heart of the most advanced and authoritative research in the field of cultural anthropology (Descola 2005; Viveiros de Castro 2009). This preliminary consideration paves the way for the second reason that encourages the field of semiotic studies to interrogate the meanings, the tightness and, in some cases, the rhetoric inherent in the multiple uses of this term. This is an opportunity to explore the positive repercussions of a close comparison with the research path of one of the scholars whose work is most frequently associated with the concept of hybrid: Bruno Latour, a celebrated theorist of the paradoxes and aporias of modernity who recently passed away. The introduction to this monographic issue of E|C aims to outline the reasons for the growing interest in the field of semiotic studies in Bruno Latour's work on the paradoxes of modernity, highlighting both the reasons for interest and those of mutual skepticism that have marked the dialogue between distinct but fruitful research perspectives. The paper traces some promising directions in contemporary semiotic research that highlight how the distance between Latour's work and the theory of signification does not consist in an unbridgeable gap on the epistemological level, but rather in a misalignment of trajectories of analysis that mainly affects the methodological level.